2013
DOI: 10.11646/phytotaxa.154.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Muscari erdalii (Asparagaceae, Scilloideae), a new species from Southern Turkey

Abstract: Muscari erdalii is described as a new species from Mersin, Southern Turkey. A description, photographs and identification key to the subgenus Leopoldia for Turkish species are given. The morphological differences between the new species and related taxa (M. tenuiflorum Tausch, M. babachii Eker & Koyuncu) are also presented. Also the karyomorphology of M. erdalii, M. tenuiflorum and M. babachii is presented and discussed. The chromosome number of the new species is 2n = 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Leopoldia are diploid (2n = 2x = 18), with the same chromosome numbers as previous studies. The chromosome number and karyotype formula of M. babachii was counted as 2n = 2x = 18 = 8m + 6sm + 2st + 2st SAT in our study, which is the same result given in our previous study (Demirci et al, 2013). Azizi et al (2016) reported the karyotype of M. comosum as 2n = 2x = 18 = 2t + (1m + 1sm) + 14m, while Ruiz Rejon et al (1990) reported its karyotype as 2n = 2x = 18 = 14m + 2sm + 2t.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Leopoldia are diploid (2n = 2x = 18), with the same chromosome numbers as previous studies. The chromosome number and karyotype formula of M. babachii was counted as 2n = 2x = 18 = 8m + 6sm + 2st + 2st SAT in our study, which is the same result given in our previous study (Demirci et al, 2013). Azizi et al (2016) reported the karyotype of M. comosum as 2n = 2x = 18 = 2t + (1m + 1sm) + 14m, while Ruiz Rejon et al (1990) reported its karyotype as 2n = 2x = 18 = 14m + 2sm + 2t.…”
Section: Discussionsupporting
confidence: 88%
“…Chromosome number 2n = 2x = 18 = 8m + 6sm + 2st + 2st (Table 2). Previous reports: 2n = 18 (Demirci et al, 2013).…”
Section: Resultsmentioning
confidence: 83%
“…Ten different bulbs of each species were investigated karyologically and 10 -15 metaphase plates were studied. Chromosome counts were obtained from somatic metaphases using a standard squash technique (Koçyiğit & Bona 2013;Demirci & al. 2013).…”
Section: Methodsmentioning
confidence: 99%
“…(Asparagaceae) is a genus of bulbous plants and has a wide distribution in Mediterranean region, Europe, Iran, Iraq and Afghanistan [1,2]. In Turkey, it is represented by 37 species, 25 of which are endemic [2,3].…”
Section: Introductionmentioning
confidence: 99%